A hologram for the king [videorecording (DVD)] - Tykwer, Tom, 1965-; Tykwer, Tom, 1965-; Hanks, Tom; Black, Alexander; Whishaw, Ben, 1980-; Choudhury, Sarita (Roadside Attractions LLC, 2016)
In a rising Saudi Arabian city, far from weary, recession-scarred America, a struggling businessman named Alan Clay pursues a last-ditch attempt to stave off foreclosure, pay his daughter's college tuition, and finally do something great.